To solve for a variable, you need to get it (x) by itself.
2x² - 4x + 5 = 6 Subtract 6 from both sides
2x² - 4x - 1 = 0 Plug this into the Quadratic Formula
a = 2 , b = -4 , c = -1
x =
![\frac{-b \pm \sqrt{b^2 - 4ac} }{2a}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-b%20%5Cpm%20%20%5Csqrt%7Bb%5E2%20-%204ac%7D%20%7D%7B2a%7D%20)
Plug in your values
x =
![\frac{-(-4) \pm \sqrt{(-4)^2 - 4(2)(-1)} }{2(2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-%28-4%29%20%5Cpm%20%5Csqrt%7B%28-4%29%5E2%20-%204%282%29%28-1%29%7D%20%7D%7B2%282%29%7D%20)
Simplify
x =
![\frac{4 \pm \sqrt{16 + 8} }{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%20%5Cpm%20%5Csqrt%7B16%20%2B%208%7D%20%7D%7B4%7D%20)
Simplify
x =
![\frac{4 \pm 2\sqrt{6} }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B4%20%5Cpm%202%5Csqrt%7B6%7D%20%7D%7B4%7D)
Simplify by removing a 2 from every term
x =
![\frac{2 \pm \sqrt{6} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20%5Cpm%20%5Csqrt%7B6%7D%20%7D%7B2%7D)
Simplify by taking the fraction apart
x =
![\frac{2}{2} \pm \frac{ \sqrt{6} }{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B2%7D%20%20%5Cpm%20%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B2%7D%20)
Change
![\frac{2}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B2%7D%20)
to 1
x = 1
![\pm \frac{ \sqrt{6} }{2}](https://tex.z-dn.net/?f=%5Cpm%20%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B2%7D%20)
Simplify
![\frac{ \sqrt{6} }{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B2%7D%20)
to
x = 1
Answer:
i dont know the answer sry
Step-by-step explanation:
srryyy
Step-by-step explanation:Let number of 49 cents =A
Let number of 33 cents=B
<u>A+B=45 equation 1</u>
1 $=100 cents
49 cents =.49 dollar
33 cents=.33 dollar
so .<u>49A+.33B=17.89 equation 2</u>
Add equation 1 and equation 2
since these are simultaneous equations
.49A+.33B=17.89
A+ B=45
so divide equation 2 by 100 we get
49A+33B=1789
A+B =45 multiply equation 1 by 33 on both the sides we get
<u>33A+33B=1485 equation 3</u>
so subtract equation 3 from equation 2 we get
49A+33B=1789 equation 2
<u>33A+33B=1485 equation 3</u>
<u>16A+0 =304</u>
16A=304
A=304/16
A=19
putting nalue of A in equation 1 we get
A+B=45
19+B=45
B=45-19
B=26
so number of 49 cent stamps are 19
and number of 33 cent stamps are 26
F(-4)=G(-4) because when the two lines cross over the f line is at the -4 and same with G
We will have the following:
*First: We determine the translation rule:
We have that the point went from (3, -4) to (0, -5), thus the translation rule would be:
![(x,y)\to(x-3,x-1)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cto%28x-3%2Cx-1%29)
Second: We apply the translation rule to the other point to determine it's image, that is:
![(8,7)\to(8-3,7-1)\to(5,6)](https://tex.z-dn.net/?f=%288%2C7%29%5Cto%288-3%2C7-1%29%5Cto%285%2C6%29)
So, the image of the second point is (5, 6).